The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1001/archpsyc.64.9.1058
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Physiological Response to a Test Meal in Purging Disorder and Bulimia Nervosa

Abstract: Purging disorder is a clinically significant disorder of eating that appears to be distinct from bulimia nervosa on subjective and physiological responses to a test meal. Findings support further consideration of purging disorder for inclusion in the classification of eating disorders. Future studies on the psychobiology of purging disorder are needed to understand the propensity to purge in the absence of binge eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
147
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 96 publications
(167 citation statements)
references
References 36 publications
17
147
3
Order By: Relevance
“…8,11,17 In addition, PD has been associated with lower scores on the TFEQ Hunger and Disinhibition scales. 8,9 Differences in hunger and disinhibition between PD and BN were maintained at 6-month follow-up as was diagnostic status, supporting the longitudinal stability of distinctions between PD and BN. 8 Finally, recent findings indicate that PD and BN demonstrate distinct subjective and physiological responses to a standardized test meal.…”
Section: Distinctiveness Of Pdmentioning
confidence: 74%
See 4 more Smart Citations
“…8,11,17 In addition, PD has been associated with lower scores on the TFEQ Hunger and Disinhibition scales. 8,9 Differences in hunger and disinhibition between PD and BN were maintained at 6-month follow-up as was diagnostic status, supporting the longitudinal stability of distinctions between PD and BN. 8 Finally, recent findings indicate that PD and BN demonstrate distinct subjective and physiological responses to a standardized test meal.…”
Section: Distinctiveness Of Pdmentioning
confidence: 74%
“…However, women with PD reported lower eating concerns, had lower scores on the Three Factor Eating Questionnaire Hunger and Disinhibition scales, and had lower depression and trait anxiety as well as lower rates of current mood disorders compared to women with BN. 8 These findings have been largely replicated in a third study by Keel et al 9,10 In addition, Keel et al 10 found comparable impairment in BN and PD and higher rates of current anxiety disorders in PD compared with BN in their third study. In a sample of treatment-seeking adolescents, Binford and le Grange 11 found no significant differences between PD and BN on measures of dietary restraint, depression, or lifetime diagnoses of depressive disorder, anxiety disorder, or substance use.…”
Section: Clinical Significance Of Pdmentioning
confidence: 81%
See 3 more Smart Citations